Shielding Privacy in the Surveillance Era: A Comparative Study of India, USA and South Africa (Law, State and Telecommunications Review, 2024)
[Purpose] The right to privacy has been gravely undermined in the pretence of “protecting national security and safety”. Although the idea of privacy has been around for a while, it has only recently come to be acknowledged as a human right. The researchers have juxtaposed the jurisprudence developed surrounding privacy in India with that of South Africa and the United States to analyse its evolution and conceptualisation.[Methodology] Comparative analysis, judgment analysis, deductive method and critical analysis have been adopted by the researchers.[Findings] It was deduced that on comparison of the three nations, South African premise of privacy is significantly stringent when compared to the other two countries i.e. India and US.[Practical Implications] The debate that commenced years ago is still going robust and revolves around whether the “right to privacy” of an individual should be prioritised before the state's utilitarianism. The Indian, American and South African governments have "valid" concerns about public safety and national security. However, the government must understand that protection must not come at the expense of the fundamental right to privacy or as a matter of fact any other human rights, especially when they are arbitrary.  Obtaining access to personal data can be exploited for nefarious and arbitrary reasons under the pretence of national security. Upon analysis, it can be deducted that on comparision of the three nations, South African conceptualisation of the premise of privacy is significantly stringent when compared to the other two countries i.e India and US. US’s structure and premise of privacy in the surveillance era looked weaker when compared to India and South Africa. India’s tenents of the same can be positioned in the centre of spectrum/scale. The article further elucidates how Pegasus and Snowden revelations reveal the weak conceptualisation of privacy in US.[Originality] There are various instances where the data is being used to monitor “targeted” people like journalists, activists and used to “silence” them. In reality, a targeted monitoring programme in accordance with global human-rights norms may be used to better address security risks like terrorism. This conceptualization of “silencing surveillance” is the original work of the researchers.